Director´s liability for unlawful profits - García Long, Sergio (2023)
Directors’ liability has certain aspects that demand a special legal treatment different from the general rules of civil liability. One such aspect is the commission of profitable wrongs, which are situations where a damage is caused intentionally to obtain a benefit. This makes compensation insufficient and requires for restitution and unjustified enrichment, and even figures of deterrence and punitive nature such as disgorgement of profits and punitive damages, which is a lively debate in comparative law.This paper analyzes the legal consequences derived from wrongs that generate illicit profits and shows the defectiveness of the current corporate regulation in this regard.